2022
DOI: 10.1002/wcms.1604
|View full text |Cite
|
Sign up to set email alerts
|

Machine intelligence for chemical reaction space

Abstract: Discovering new reactions, optimizing their performance, and extending the synthetically accessible chemical space are critical drivers for major technological advances and more sustainable processes. The current wave of machine intelligence is revolutionizing all data-rich disciplines. Machine intelligence has emerged as a potential game-changer for chemical reaction space exploration and the synthesis of novel molecules and materials. Herein, we will address the recent development of data-driven technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 205 publications
(335 reference statements)
0
70
0
Order By: Relevance
“…45,46 In the future, we plan to generate datasets for systems with more atoms, and to evaluate anharmonic partition functions to train new estimators. Transfer 47 or delta 48 learning might be used to accelerate these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In the future, we plan to generate datasets for systems with more atoms, and to evaluate anharmonic partition functions to train new estimators. Transfer 47 or delta 48 learning might be used to accelerate these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Strieth-Kalthoff et al demonstrated the benefit that emerges from the usage of real experimental data for machine learning-based chemical yield predictions [12] while the prediction of reaction outcomes and yields remains a challenge [49]. Nonetheless, there have been impressive developments using attention-based deep learning methods to explore the chemical reaction space [50]. Schwaller et al have shown that the attention matrix weights of transformers that have been trained on unlabelled chemical reaction data can be used to determine accurate atom mappings [51].…”
Section: Digital Transformation Of Synthetic Chemistrymentioning
confidence: 99%
“…Again, the described advances are exemplary cases of the synergy of deep learning-based models and the availability of training data. There are datasets extracted from US patents [52,[56][57][58][59], the scientific literature [60] and high-throughput experiments (HTE) [61] available [50]. Recently, the Open Reaction Database (ORD) has been launched as a platform to replace unstructured reaction data in the supporting information of publications [62].…”
Section: Digital Transformation Of Synthetic Chemistrymentioning
confidence: 99%
“…Such methods date back to the 60's and the early work of Corey, 3 although the research has intensified in the last decade due to the increased interest in machine learning and artificial intelligence. 4 At the heart of retrosynthesis analysis is a method that is capable of predicting disconnections on a compound and thereby producing precursors. Such methods are typically referred to as one-step retrosynthesis or single-step retrosynthesis.…”
Section: Introductionmentioning
confidence: 99%